Thomas Mann's war : literature, politics, and the world republic of letters - Boes, Tobias, 1976- (Cornell University Press, 2019)
"During the period of his American exile in the 1930s and 1940s, the German author Thomas Mann became one of the most prominent anti-fascists in the United States, and in so doing forever transformed our understanding of what a modern writer is and should be doing"--